The liberal ideology and some English South African novelists - Watson, Stephen (Department of English Language and Literature, 2015)
This thesis has been written in an attempt to answer a question which came to mind when I first began reading white English south African literature. The question itself was quite simple: why is this literature like it is, and, more particularly, why is it a body of work whose quality is generally so mediocre? There is a general critical consensus that it is mediocre, and all the more so when it is judged in the light of standards set by modern European and American literature.